2022
DOI: 10.3390/educsci12020131
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Classroom in Senior High School Textile Education to Enhance Students’ Learning Achievement and Self-Efficacy

Abstract: The study analysed the impact of the flipped classroom (FC) approach on weaving experience, self-efficacy and students’ learning achievement. To achieve this purpose, a quasi-experimental (pre-test/post-test) design, with a control group and an experimental group, was implemented. A mixed methods approach was used to evaluate the outcomes of the intervention. Forty- four first year senior high school students of an elective textile education subject participated in the study. An academic achievement test and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…The instructor guides students to participate in learning, apply knowledge gained from concepts, and equip learners with 21st-century skills. Students become more familiar with new knowledge and participate in class activities through student collaboration to improve their creativity, critical thinking, and problem-solving skills [31,32].…”
Section: Related Literaturementioning
confidence: 99%
“…The instructor guides students to participate in learning, apply knowledge gained from concepts, and equip learners with 21st-century skills. Students become more familiar with new knowledge and participate in class activities through student collaboration to improve their creativity, critical thinking, and problem-solving skills [31,32].…”
Section: Related Literaturementioning
confidence: 99%
“…Selfefficacy is an individual's subjective judgment and evaluation about whether they can achieve a specific accomplishment or complete a particular job [26]. It has been noted that self-efficacy is not simply a verbal expression of university students based on their self-perception and self-competence; it is produced via cognitive processing, and individuals with different self-efficacies produce different motivated behaviors for learning [27]. General self-efficacy, as the inner cognition of individual subjective achievement and competence, may affect the motivation choice of university students to learn conformity [28].…”
Section: Self-efficacy Researchmentioning
confidence: 99%
“…The sample size for the university student learning conformity study was first determined based on a priori power analysis, setting α fixed at the conventional level of 0.05 and powers of 0.80 [27], as well as assuming a small effect size (r = 0.20) [27]. The power analysis indicated that the minimum sample size required for this study was n = 194.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Studies show that flipped instruction increases students' active learning roles in constructing their own knowledge (Awidi & Paynter, 2019). Many empirical studies on the effectiveness of the flipped learning as an instructional approach found increased student academic achievement in chemistry (Olakanmi, 2017;Oppong et al, 2022;Rohyami & Huda, 2020), development of critical thinking skills (Boateng et al, 2022;Munzil et al, 2020) due to the active engagement and interactive nature of the approach.…”
Section: Flipped Learningmentioning
confidence: 99%